Insights into Chinese Agriculture - Zhang, Yunhua (Shanghai Far East Publishers, 2018)
This book uses simple economic theories to explain how China's agricultural economic phenomena exists in reality. It also helps the reader to get a clear understanding of economic phenomena, insight into the "hog cycle" and "food safety," as well as other economic and social phenomena. The language of this book is not only easy to understand, but also uses ancient poetry and humor to make the subject interesting, as it speaks to the history and current situation of Chinese agriculture. It also opens a window for the people to read about agriculture. This is a unique book on agricultural science that fills an important gap in works on agricultural science and agricultural economics.
Chapter 1 Does China Have Enough to Eat -- Chapter 2 The Problem of Food Safety -- Chapter 3 Rural Land System and Rights -- Chapter 4 Can Farming Make Money -- Chapter 5 Who Will Till the Land and How Will They Till It.
P.B
Description based on publisher-supplied MARC data.
Keywords: Agricultural economics; Agriculture; Welfare economics; Agricultural Economics; Agriculture; Social Choice/Welfare Economics/Public Choice/Political Economy